Investigation of tick vectors of Hepatozoon canis in Brazil - Demoner, Larissa de Castro [UNESP]; Rubini, Adriano Stefani [UNESP]; Paduan, Karina dos Santos [UNESP]; Metzger, Betina [UNESP]; Paula Antunes, Joao Marcelo Azevedo de [UNESP]; Martins, Thiago Fenandes; Camargo Mathias, Maria Izabel [UNESP]; O'Dwyer, Lucia Helena [UNESP] (Elsevier B.V., 2013)
Hepatozoon canis is a common apicomplexan parasite of dogs. In Brazil, in addition to Rhipicephalus sanguineus, Amblyomma ovate, Amblyomma cajennense, and Rhipicephalus (Boophilus) microplus have been suggested to act as vectors. The present study aimed to evaluate, under controlled conditions, the acquisition of H. canis by A. ovate, R. sanguineus, and A. cajennense after feeding on naturally infected dogs. Cytological and histophatological examinations were performed to recover oocysts and other sporogonic stages of the protozoan from the experimentally infected nymphs and adults. None of the R. sanguineus (n = 30) or A. cajennense nymphs (n = 15) that were dissected after feeding on H. canis naturally infected dogs became infected by the hemoparasite. Likewise, none of the R. sanguineus (n = 165) and A. cajennense (n = 114) adult ticks that were fed as nymphs on dogs demonstrated infection. Additionally, A. cajennense adult ticks were incapable of acquiring the infection, since no parasite was found in 62 adults that fed on H. canis-infected dogs. With regard to A. ovate ticks, 2 different infestations were carried out. Firstly, a dog with naturally occurring hepatozoonosis was infested with A. ovate adults originating from Rondonia, Brazil. Ticks fed to full engorgement. A total of 31 adults was collected from the dog and dissected on the third day after natural detachment. Oocysts were detected in 13 (42%) of the ticks. The second experimental infestation was carried out using adult ticks originating from Sao Paulo, Brazil. Surprisingly, of the 103 dissected ticks, only one (1%) contained oocysts in the hemocoel. No other sporogonic stage was found. Results indicate that different strains of A. ovate ticks may exist in Brazil with different susceptibilities to pathogens. Furthermore, it is possible that R. sanguineus and A. cajennense have little or no importance in the transmission of H. canis in rural areas of Brazil. (C) 2013 Elsevier GmbH. All rights reserved.
Keywords: Amblyomma cajennense; Amblyomma ovale; Rhipicephalus sanguineus; Hepatozoon canis; Transmission; Brazil